Broder Giovanni och judarna - Belinki, Karmela (Nordisk judaistik, 2005)
This paper deals with the portrayal of the Jew in a Finnish comic magazine edited by the pseudonym Veli Giovanni (Brother Giovanni) for more than thirty years (1919-1950). The stereotypical and negative image of the Jew hardly changed from the very first issue to the last. There were caricatures of the Jew in almost every issue of the magazine. Because of its popularity it was probably not completely without influence, although it claimed to be innocent entertainment and did not confess to any political attachment. The physiognomy of the Jew follows the classical pattern (big nose, curly hair, short body). The character is congruent with the body. The Jew is a slimy figure, constantly trying to cheat others. He is greedy and his main interest is money. He is an internationalist, a non-patriot, and he speaks Finnish with a strange accent and using his own idiolect (Jewish gibberish). He is the total opposite of the real Finn and an alien in Finnish society. The son of the Jew is the adult in miniature.